THE PROSPECTIVE ROLE OF DA’AWAH BI AL-HIKMAH IN AVERTING INTER-RELIGIOUS VIOLENCE IN NIGERIA - Ummaru, Ammaru; Nura Muhammad Iliyas; Mohd Farid Mohd Sharif (Socio Religia, 2025)
It has been unanimously agreed by the researchers that one of the direct causes of inter-religious violence between the Christians and Muslims in Nigeria is reckless religious preaching that attack the creed of other religion and its followers. Such preaching often arouses provocation, annoyance and infuriation from the other side. The fact that both Islam and Christianity are religions of strong proselytization, enjoined their followers to invite other people into their folds. Both Islam and Christianity consider the task of inviting others into their fold as noble work and obligatory duty upon their respective followers. The aim of this paper is to analyze the negative role of provocative preaching in causing inter-religious tension between the Muslims and Christians in the country and showcase the efficacy of employing the Da’awah bi al-Hikmah (as enshrined in the Qur’an and Sunnah) in averting preaching related violence in the future. The research adopted analytical method where primary and secondary data from the Qur’an, hadith, academic books, journal articles, conference papers, dissertations, online sources etc were collected and analyzed. The paper discovered that some of the inter-religious violence such as that of Kafancan in 1987 and Maitatsine riot in 1980s were triggered by the reckless preaching of some fundamentalist preachers. The paper also demonstrated the prospective capacity of Da’awah bi al-Hikmah in deterring the preaching related violence in the country. The paper recommended for regulation, screening, training and certification of both preachers and the contents of the preaching in the country.